2018
DOI: 10.1182/blood-2018-99-111140
|View full text |Cite
|
Sign up to set email alerts
|

Erythroferrone Inhibits the Induction of Hepcidin By BMP6

Abstract: Decreased hepcidin mobilizes iron, which facilitates erythropoiesis, but excess iron is pathogenic in beta-thalassemia and other iron-loading anaemias. Erythropoietin (EPO) enhances erythroferrone (ERFE) synthesis by erythroblasts, and ERFE suppresses hepatic hepcidin production, through an unknown mechanism. The BMP/SMAD pathway in the liver is critical for control of hepcidin, and we show that EPO suppressed hepcidin and other BMP target genes in vivo in a partially ERFE-dependent manner. Furthermore, recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…Figure S6). Erfe has been shown to suppress BMP/SMAD signaling in vivo and in vitro and to inhibit hepcidin induction by BMP6 (78). Thus our data suggest that cFGF23 decreases hepcidin induction by LPS by increasing Erfe, and possibly suppressing the BMP6/SMAD pathway.…”
Section: Discussionsupporting
confidence: 54%
“…Figure S6). Erfe has been shown to suppress BMP/SMAD signaling in vivo and in vitro and to inhibit hepcidin induction by BMP6 (78). Thus our data suggest that cFGF23 decreases hepcidin induction by LPS by increasing Erfe, and possibly suppressing the BMP6/SMAD pathway.…”
Section: Discussionsupporting
confidence: 54%
“…Recent evidence indicates that ERFE inhibits hepcidin expression by antagonizing select members of the bone morphogenetic protein (BMP) family (Arezes et al, 2018;Wang et al, 2020). BMP signaling in hepatocytes regulates hepcidin transcription in response to plasma iron concentrations and hepatic iron stores, and the pathological loss of BMP signaling causes hepcidin deficiency and systemic iron overload (Canali et al, 2017;Koch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, BMP2 and 6 secreted by the sinusoidal endothelial cells in the liver are the key regulators of hepcidin transcription (Wang et al, 2020). ERFE lowers hepcidin transcription by sequestering the BMP2/6 heterodimer (Wang et al, 2020), but ERFE was also reported to bind other BMPs including BMP2, 4, 5, 6 and 7 (Arezes et al, 2020a;Arezes et al, 2018). Considering that BMP signaling has pleiotropic effects beyond its role in iron homeostasis, the endocrine effects of ERFE may not be limited to hepcidin regulation in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of erythropoiesis is a fundamental driving force in modulating hepcidin expression, especially when iron demand increases under enhanced erythropoiesis. Under this setting, ERFE is greatly induced by EPO to suppress hepcidin through binding to BMPs 27,41 . However, whether ERFE is involved in regulating hepcidin expression during normal and abnormal pregnancy remains unkown.…”
Section: Resultsmentioning
confidence: 99%
“…ERFE, encoded by Fam132b , is a glycoprotein hormone generated by erythroblasts due to the stimulation of erythropoietin (EPO) in the bone marrow and spleen 24–26 . Recently, it was discovered that ERFE competes with BMP6 for binding to BMP receptors on the surface of hepatocytes, resulting in compromised BMP‐SMAD1/5/8 signalling in driving hepcidin expression 27 . As a consequence, iron absorption and iron recycling are enhanced to promote the availability of iron supply for the erythropoiesis 27,28 .…”
Section: Introductionmentioning
confidence: 99%